STRESS, ANXIETY AND DEPRESSION DURING AND AFTER FOUR YEARS OF COVID-19 PANDEMIC: A PROSPECTIVE STUDY IN EASTERN INDIA - Shaswata Mandal; Rudraprasad Acharya; Meghadipa Mandal (Journal of Public Health Research and Community Health Development, 2026)
Background: Psychiatric morbidity has shown statistically significant prevalence in COVID-19 patients during and after the disease. This study focuses on assessing the levels of depression, anxiety, and stress among patients hospitalized with COVID-19 and evaluating their mental health status after four years. Purpose: The objective of the study was to grade degree of severity of depression, anxiety and stress with degree of severity of COVID-19 infection and their correlation with comorbidities and socio-demographic profiles. Methods: An observational study was conducted in COVID-19 in-patient ward. The patients were graded into mild, moderate and severe cases of COVID-19 infection. The Depression Anxiety Stress Scale-21 (DASS-21) questionnaire was used to classify subjects into normal, mild, moderate, and severe categories for each psychological domain. Various socio-demographic profiles were also recorded. IBM SPSS Statistics version 25 software was used to compare these parameters. These same patients were followed for four years to assess changes in mental health status. Results: Initially, 75.5% of patients had mild symptomatology for COVID-19 infection. There were proportionate numbers of mild, moderate and severe depression cases, whereas majority had severe anxiety in contrast to mild stress symptoms among study subjects. A significant association was found between the severity of COVID-19 infection and the levels of depression, anxiety, and stress. 50 patients out of a total of 76 showed no symptoms of any mental illness after four years. Conclusion: Mental health should be prioritized at the outset to identify and safeguard those at risk and promote long-term resilience.